STUDENTS’ DIFFICULTIES IN LEARNING VOCABULARY THROUGH VIDEO CLIP (A CASE STUDY IN SMK KESEHATAN SAMARINDA) - Bali Geroda, Godefridus; Widiastuti, Yovia Rosandow (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
Vocabulary is a part of the language. It is important for the students to learn vocabulary. Learning vocabulary through video is one of many strategies that teacher can use in teaching vocabulary to the students. The aim of this study is to find out students’ difficulties in learning vocabulary through video clips, in order to find students’ difficulties in learning vocabulary through video clips, the researcher will use case study as design with qualitative approach. The subjects of this study are the first-grade students in SMK Kesehatan Samarinda. The researcher will use two kind of supporting instrument to collect the data; interview and observation. The output of this study is expected to give useful contribution to existing theories of vocabulary. Besides, practically, this study will provide more insight about problems in learning vocabulary as well as students’ effort toward the problems to English teachers so that they are able to design appropriate strategy for better leaning vocabulary. For students, this study will help them in figuring out their weaknesses so that they can improve their vocabulary effectively. For future researcher, this study is hoped to become a reference for those who investigate similar topic. Finally, this study is planned and expected to be published on Scopus journal.